Peritoneal microbiome in end-stage renal disease patients and the impact of peritoneal dialysis therapy - Simões-Silva, L (2020)
Factors influencing the occurrence of peritoneal dialysis (PD)-related infections are still far from fully understood. Recent studies described the existence of specific microbiomes in body sites previously considered microbiome-free, unravelling new microbial pathways in the human body. In the present study, we analyzed the peritoneum of end-stage kidney disease (ESKD) patients to determine if they harbored a specific microbiome and if it is altered in patients on PD therapy. We conducted a cross-sectional study where the peritoneal microbiomes from ESKD patients with intact peritoneal cavities (ESKD non-PD, n = 11) and ESKD patients undergoing PD therapy (ESKD PD, n = 9) were analyzed with a 16S rRNA approach. Peritoneal tissue of ESKD patients contained characteristically low-abundance microbiomes dominated by Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. Patients undergoing PD therapy presented lower species richness, with dominance by the Pseudomonadaceae and Prevotelaceae families. This study provides the first characterization of the peritoneal microbiome in ESKD patients, bringing new insight to the human microbiome. Additionally, PD therapy may induce changes in this unique microbiome. The clinical relevance of these observations should be further explored to uncover the role of the peritoneal microbiome as a key element in the onset or aggravation of infection in ESKD patients, especially those undergoing PD.